Akuntansi Era Digital: Keterampilan dan Persepsi Akurat Mahasiswa di Dunia Online - Roshani Roshani; Novi Sentiya; Munandar Munandar (Indonesian Accounting Literacy Journal, 2026)
This study examines the relationship between students’ digital competence and their perceptions of Accounting Information System (AIS) quality in the use of Accurate Online within the digital era. A quantitative approach was employed by distributing questionnaires to accounting students. Digital competence was measured using the DigComp 2.2, while AIS quality was evaluated based on ISO/IEC 25010, including Function Suitability, Performance Efficiency, Usability, Reliability, and Security. Data were analyzed using correlation, hypothesis testing, and Cartesian diagram analysis. The findings reveal a strong and significant relationship between digital competence and the use of Accurate Online. However, the Cartesian analysis indicates a gap between importance and satisfaction across several dimensions. Function Suitability and Security fall into Quadrant A, indicating high importance but low satisfaction, thus requiring immediate improvement. Performance Efficiency is positioned in Quadrant C, reflecting both low importance and low satisfaction, mainly due to technical issues such as system lag. In contrast, Usability and Reliability are categorized in Quadrant D, suggesting low importance but high satisfaction. These results are influenced using the free version of Accurate Online, which offers limited features and functionality. The study emphasizes the need to enhance system functionality and security, as well as to strengthen students’ digital competence and institutional infrastructure to better support accounting education in the digital era.